PENGARUH FINANCIAL LEVERAGE, DANA PIHAK KETIGA DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP PROFITABILITAS (Studi kasus pada bank Indonesia yang terdaftar di BEI periode 2012-2015) - Nasrudin Islam; Rony Malavia Mardani; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis reseach aimed to examine the effect of Financial leverage, Third party funds, interest rate of bank Indonesia certificates on bank Profitability. The sampel used in this reseach is a commercial bank listed on the Indonesia Stock Exchange 2012 to 2015 period. To obtain valid results, the sampling technique used in this study is a purposive sampling method in order to obtain a sampel of 12 banks. Data analysis method used is multiple linear regression analysis, normality test, classic assumption (multicollinearity test, heteroskedastistas test, autocorrelation test), the hypotheses using partial test (t test) and a simultaneous test (f test).T test result showe that Financial leverage significant impact on Profitability, Third party funds positive and significant impact on Profitability, interest rate SBI significant on impact Profitability. While the F test shows that Financial leverage, Third party funds and SBI interest rates together have a significant effect on Profitability.Keywords : financial leverage, Third Party funds, interest rate of Bank Indonesia Certificates (SBI), Profitability. X